The Associations between Parenting Styles, Family Power Structure, and Students’ Emotional Autonomy with the Mediating Role of Parent-Adolescent Relationship - Mousavi, Shokoufeh; Shahsavari, Mahmoud Reza; Mirian, Zeinab Sadat (Social Determinants of Health, 2024)
Background: During adolescence, achieving emotional autonomy is crucial for successful identity formation, individuation, and the transition to adulthood. The current investigation examines the associations between parenting styles, family power structures, and emotional autonomy in students, with a particular focus on the mediating role of parent-adolescent relationships. Methods: : This study utilized a descriptive correlational design and structural equation modeling (SEM) to examine the hypothesized relationships. A cluster sample of 363 high school students in Isfahan was selected. Data were collected using four standardized instruments: the Emotional Autonomy Scale, the Parenting Style Questionnaire, the Power Structure of the Family Questionnaire, and the Parent-Child Relationship Survey. Pearson correlation coefficients were initially computed to assess bivariate associations, followed by SEM to test the hypothesized mediation model. Results: The findings indicate that both permissive and authoritarian parenting styles were significantly associated with a family power structure characterized by parental dominance (P<0.001). Additionally, a positive correlation was found between the quality of the parent-adolescent relationship and students' emotional autonomy (P<0.001). Importantly, the analysis revealed a significant indirect effect of the authoritarian parenting style on students' emotional autonomy, mediated by the parent-adolescent relationship (P<0.001). Conclusion: This study highlights the crucial role of parenting styles and family power structures in shaping students' emotional autonomy. The findings suggest that while both permissive and authoritarian styles are associated with the family power structure, only the authoritarian style seems to exert its influence indirectly through the parent-adolescent relationship.